The conservation state of the Sassi of Matera site (Southern Italy) and its correlation with the environmental conditions analysed through spatial analysis techniques - Gizzi, Fabrizio Terenzio; Sileo, Maria; Biscione, Marilisa; Danese, Maria; Alvarez de Buergo, Monica (Journal of cultural heritage, 2016)
The current study aims to analyse the conservation state of the Sassi of Matera site (Southern Italy), a place inscribed on the UNESCO World Heritage List since 1993 (the Sassi and the Park of the Rupestrian Churches of Matera) and recently awarded 2019 European Capital of Culture. Furthermore, the article considers the influence of some of the causative factors controlling the Matera building conservation state, paying particular attention to the site microclimatic conditions such as the insolation and winds. We studied this subject through a new methodology that makes a combined use both of stone decay data gained from the extensive field assessments of the visible weathering forms catalogued in an ad hoc questionnaire and GIS advanced spatial analysis techniques such as Map Algebra and Kernel Density Estimation. The research puts into evidence that the Sassi of Matera shows a fair state of conservation that is conditioned by the wind/rain actions and sun exposure. Besides, just the already well known facts that the surfaces facing north seem to be most influenced by the wind/rain actions; and that, on the contrary, the decay of the walls facing south seems to be guided mainly from the sun exposure, put into evidence the importance of locating the intensities of the decays in any urban tissue or any site in order to plan conservation interventions and prioritize actions and the usefulness of the spatial analysis techniques and data processing.